Vaccination strategies for patients under monoclonal antibody and other biological treatments: an updated comprehensive review based on EMA authorisations to January 2024 - Rivera-Izquierdo, Mario; Morales-Portillo, Arturo; Guerrero-Fernández de Alba, Inmaculada; Fernández-Martínez, Nicolás Francisco; Schoenenberger-Arnaiz, Joan Antoni; Barranco-Quintana, José Luis; Valero-Ubierna, Carmen (Expert review of vaccines, 2024)
Monoclonal antibodies (mAbs) and other biological agents are being increasingly approved in the last years with very different indications. Their highly heterogeneous immunosuppressive effects, mechanisms of action and pharmacokinetics require comprehensive individualized vaccination schedules. Vaccination for immunocompromised patients. Prevention and treatment with mAbs and other biological therapies. Current recommendations on vaccine schedules for patients under mAbs or other biological treatments are based on expert opinions and are not individualized according to each vaccine and treatment. No studies are focusing on the high heterogeneity of these agents, that are exponentially developed and used for many different indications. Recent paradigm changes in vaccine development (boosted by the COVID-19 pandemic) and in the mAbs use for prophylactic purposes (changing 'vaccination' by 'immunization' schedules) has been witnessed in the last years. We aimed at collecting all mAbs used for treatment or prevention, approved as of 1 January 2024, by the EMA. Based on available data on mAbs and vaccines, we propose a comprehensive guide for personalizing vaccination. Recent vaccine developments and current population strategies (e.g. zoster vaccination or prophylactic nirsevimab) are discussed. This review aims to be a practical guideline for professionals working in vaccine consultations for immunosuppressed patients.